Impacto socioeconómico de la covid-19 en el turismo gastronómico de la parroquia Canoa del cantón San Vicente - Chávez Macías, Ladys Nathaly (2022)
The purpose of this research is to publicize the impact of the Covid-19 pandemic on the local economy of the parish of Canoa, located in the canton of San Vicente, in this way, the need arises to carry out a study that shows the current socioeconomic situation before the episodes of the existing pandemic in the gastronomic tourism sector of the parish, the methodology was established through three phases of development, it is necessary to employ a bibliographic and field research, for the respective analysis and synthesis of the techniques applied in the place of the facts; the realization of the survey affirmed the negative impact of the Covid-19 in the local economy of the parish of Canoa, due to the suspension of tourist activities causing a reduction in sales and revenues of gastronomic establishments. The results established the current situation of informal restaurants in the parish, and the development of the 5w+1h tool allowed to develop the proposal of strategies aimed at improving the socio-economic situation of the community in the face of the shortcomings found.